2006
DOI: 10.1021/ic060487y
|View full text |Cite
|
Sign up to set email alerts
|

Helices versus Zigzag Chains:  One-Dimensional Coordination Polymers of AgIand Bis(4-pyridyl)amine

Abstract: Five one-dimensional coordination polymers were prepared by the reaction of a bent bridging ligand, bis(4-pyridyl)amine (bpa), with an extensive series of AgX salts (X = CF3SO3, PF6, ClO4, NO3). The 1D polymer networks formed with AgCF3SO3 (1), AgPF6 (2.MeCN), and AgClO4 (3.2MeCN) all incorporated MeCN and were found to adopt a zigzag arrangement. The networks formed with AgClO4 (4) and AgNO3 (5) did not contain any solvent and adopted a single-stranded helical arrangement. Two-dimensional H-bonding networks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 75 publications
0
25
1
Order By: Relevance
“…In Figure 4 we show two examples of crystal structures retrieved from the CSD (codes IMUYEU [8d] and EQOYIS [20] ) in which the anion-p interaction is evident and play a prominent role in the crystal packing. Further experimental evidence can be extracted from the recent and elegant work of Hanton and coworkers [9,21] who performed an encapsulation of anions by a uniform mode of anion-p binding in isomorphous (4,4) nets formed from Ag I salts and bis(4-pyrimidylmethyl)sulfide. In summary, the results derived from the high-level ab initio calculations reported herein reveal that the anion binding properties of pyridine (1) and pyrazine (2) change when they are coordinated to silver(I), compounds 3 and 4 respectively.…”
Section: Compoundmentioning
confidence: 99%
“…In Figure 4 we show two examples of crystal structures retrieved from the CSD (codes IMUYEU [8d] and EQOYIS [20] ) in which the anion-p interaction is evident and play a prominent role in the crystal packing. Further experimental evidence can be extracted from the recent and elegant work of Hanton and coworkers [9,21] who performed an encapsulation of anions by a uniform mode of anion-p binding in isomorphous (4,4) nets formed from Ag I salts and bis(4-pyrimidylmethyl)sulfide. In summary, the results derived from the high-level ab initio calculations reported herein reveal that the anion binding properties of pyridine (1) and pyrazine (2) change when they are coordinated to silver(I), compounds 3 and 4 respectively.…”
Section: Compoundmentioning
confidence: 99%
“…There is also an Ag-Ag interaction [Ag1-Ag1 ii = 3.2883 (10) Å ; Fig. 2b], which is longer than that reported for the silver complex {[Ag(bpa)]PF 6 ÁMeCN} n [Ag-Ag = 3.2669 (5) Å , where bpa is bis(pyridin-4-yl)amine; Cordes et al, 2006], but shorter than that found in [Ag(dpa)], where Hdpa is 4,4 0 -dipyridylamine (Ag-Ag = 3.788 Å ; Rarig & Zubieta, 2002). The Ag-Ag interaction means that there is a seesaw coordination environment around each Ag atom.…”
Section: Resultsmentioning
confidence: 81%
“…The two rings of the chelating ligand are almost coplanar (angle between meanplanes = 1. [24][25][26][27][28][29][30][31], we reacted 1 with silver nitrate. This furnished a crystalline product (5) in 69% yield [32].…”
Section: Here]mentioning
confidence: 99%